A Multimodality Strategy for Cardiovascular Risk Assessment: Performance in Two Population-Based Cohorts - de Lemos, James A. (Circulation, 2017)
BACKGROUND: Current strategies for cardiovascular disease (CVD) risk assessment among adults without known CVD are limited by suboptimal performance and a narrow focus on only atherosclerotic CVD (ASCVD). We hypothesized that a strategy combining promising biomarkers across multiple different testing modalities would improve global and atherosclerotic CVD risk assessment among individuals without known CVD. METHODS: We included participants from the Multi-Ethnic Study of Atherosclerosis (MESA, n=6621) and Dallas Heart Study (DHS, n=2202) who were free from CVD and underwent measurement of left ventricular hypertrophy by electrocardiogram (ECG-LVH), coronary artery calcium (CAC), N-terminal pro B-type natriuretic peptide (NT-proBNP), high-sensitivity cardiac troponin T (hs-cTnT) and high-sensitivity C-reactive protein (hs-CRP). Associations of test results with the global composite CVD outcome (CVD death, myocardial infarction [MI], stroke, coronary or peripheral revascularization, incident heart failure or atrial fibrillation) and ASCVD (fatal or nonfatal MI or stroke) were assessed over > 10 years of follow-up. Multivariable analyses for the primary global CVD endpoint adjusted for traditional risk factors plus statin use and creatinine (base model). RESULTS: Each test result was independently associated with global composite CVD events in MESA after adjustment for the components of the base model and the other test results (p< 0.05 for each). When the five tests were added to the base model, the c-statistic improved from 0.74 to 0.79 (p=0.001), significant integrated discrimination improvement (0.07, 95% CI 0.06–0.08, p<0.001) and net reclassification improvement (0.47, 95% CI 0.38–0.56, p=0.003) were observed, and the model was well calibrated (χ2=12.2, p=0.20). Using a simple integer score counting the number of abnormal tests, compared with those with a score of 0, global CVD risk was increased among participants with a score of 1 (adjusted HR 1.9, 95% CI 1.4–2.6), 2 (HR 3.2, 95% CI 2.3–4.4), 3 (HR 4.7, 95% CI 3.4, 6.5) and ≥4 (HR 7.5, 95% CI 5.2–10.6). Findings replicated in DHS and were similar for the ASCVD outcome. CONCLUSIONS: Among adults without known CVD, a novel multimodality testing strategy using ECG-LVH, CAC, NT-proBNP, hs-cTnT and hs-CRP significantly improved global CVD and ASCVD risk assessment.